LGBT research in general and Islamic secondary education: student characteristics and perceptions - Boy, Elman; Fadhillah, Rana (Universitas Aisyah Pringsewu, 2023)
Background: The estimated number of LGBT individuals in Indonesia has reached 7.5 million, with one of the contributing factors being the taboo surrounding discussions on deviant sexual behaviors, particularly among teenagers. Purpose: The purpose of this study is to determine whether there is an effect of education on the perception of adolescents in Medan City regarding Lesbian, Gay, Bisexual, and Transgender (LGBT) individuals. Methods: This study employed a quasi-experimental design with a posttest-only control group design. The sampling method used in this research was non-probability sampling, specifically the purposive sampling technique. The research was conducted in four schools in Medan, comprising two public high schools and two Islamic-based secondary schools. The research respondents were 12th-grade students who met the inclusion and exclusion criteria. In the intervention group, a 20-minute PowerPoint presentation on LGBT was delivered to the entire class. Data were collected through a validated questionnaire consisting of 17 questions. Results: The total number of respondents was 224. The hypothesis testing on the influence of education on students' perceptions of LGBT, using the Mann-Whitney test, yielded a p-value of 0.01, indicating that the hypothesis was accepted. The hypothesis testing on the background of the school using the Mann-Whitney test resulted in a p-value of 0.01, indicating that the hypothesis was rejected. Conclusion: There is an influence of education on teenagers' perceptions of LGBT, and there is no difference in teenagers' perceptions of Lesbian, Gay, Bisexual, and Transgender (LGBT) based on the background of the school.